2013
DOI: 10.1088/0031-9155/59/1/203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coil orientation on the electric field induced by TMS over the hand motor area

Abstract: Responses elicited by transcranial magnetic stimulation (TMS) over the hand motor area depend on the position and orientation of the stimulating coil. In this work, we computationally investigate the induced electric field for multiple coil orientations and locations in order to determine which parts of the brain are affected and how the sensitivity of motor cortical activation depends on the direction of the electric field. The finite element method is used for calculating the electric field induced by TMS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
134
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(151 citation statements)
references
References 45 publications
(44 reference statements)
12
134
0
Order By: Relevance
“…However, this assumption is not universally held in the field. In particular, several authors have suggested that the normal component of the electric field (Fox et al, 2004; Janssen et al, 2015; Laakso et al, 2014) is the determinant of the stimulation area, not the field strength. These models differ somewhat in the prediction of stimulation areas, with absolute field strength predicting strongest stimulation at the gyral crowns (Opitz et al, 2011; Thielscher et al, 2011), where the normal component model predicting peak stimulation deeper in the sulci (Fox et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, this assumption is not universally held in the field. In particular, several authors have suggested that the normal component of the electric field (Fox et al, 2004; Janssen et al, 2015; Laakso et al, 2014) is the determinant of the stimulation area, not the field strength. These models differ somewhat in the prediction of stimulation areas, with absolute field strength predicting strongest stimulation at the gyral crowns (Opitz et al, 2011; Thielscher et al, 2011), where the normal component model predicting peak stimulation deeper in the sulci (Fox et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the same motor cortex area in the sulcus of M1 (Laakso et al, 2014) is being activated here as in other studies using tACS of the motor cortex with a comparable electrode montage (Moliadze et al, 2010; Chaieb et al, 2011). When applying a posterior-to-anterior (PA)-directed current via TMS, it first activates the cortical layer 1 ending in layer 6, thus depolarizing the soma of pyramidal tract cells (Jefferys, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not necessarily true: Recent studies have proposed that a subcomponent of the electric field that is induced by TMS can best predict stimulation outcomes in the motor cortex (Laakso et al 2014; Janssen et al 2015). This subcomponent is perpendicular to and directed into the cortical surface and, for TMS, maximally affects neurons situated in the sulcal wall.…”
Section: Discussionmentioning
confidence: 99%